An Effort to Improve Student Activity in Thematic Learning Through Contextual Teaching-Learning Model with Powerpoint Media in Elementary School - Rusmawati Rusmawati (Universitas Tanjungpura, 2022)
The problem in learning in Classroom Action Research is that students are less active and have not actively participated with their peers in class. In addition, students pay less attention when the teacher explained the learning topic, students are embarrassed to ask questions, students have not been able to do constructivism learning, students have not been able to associate the material learned with their daily life. The alternative learning presented to learners is thematic learning using contextual teaching and learning (CTL) models with powerpoint media to carry out learning according to thematic. We expected that there will be an increase in learning activities and learning outcomes. This research aimed to increase student learning activities by applying a contextual teaching-learning model with PowerPoint in sixth grade of elementary school students. This type of research is CAR (Classroom Action Research). The paerticipants of this study were sixth grade students of State Elementary School (SDN) 45 Sungai Raya, which amounted to 11 students. Data collection techniques were carried out through interview, observation, and documentation. The procedure of CAR was carried out through 4 stages, namely planning, implementation, observation, and reflection. The data that has been obtained was described. The results showed an increase in the learning activity. It can be proven by the results of the achievement of indicators of student learning activity as follows: physical activity increased from 54.54% in cycle I to 100% in cycle II, mental activity increased from 45.45% in cycle I to 81.81% in cycle II, emotional activity increased from 54.54% cycle I to 100% cycle II. This study concluded that applying contextual teaching and learning models with PowerPoint media can improve the learning activities of elementary school students in sixth grade SDN 45 Sungai Raya.